Critical Analysis of Regulation 1031/2010 on the auctions of allowances (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this work the main aspects of the Regulation 1031/2010, on the timing, administrationand other aspects of auctioning of greenhouse gas emission allowances pursuant to Directive 2003/87, are analyzed. The work is focused on the general goals of the Regulation (rules on bids and clearing price, conduct of auctions, determination of the annual volume of allowances to be auctioned, access to the auctions),and on relevant issues concerning the subjective elements (Member States, auctioneer,auction platform, auction monitor) and objective elements.
Keywords: climate change; emission allowances trading system; auction.